Clinical, radiological, laboratory and bronchoscopic features characterizing each type of bronchogenic carcinoma - Hafez, Manal R.; Abo-Elkheir, Omaima I. (International Journal of Research in Medical Sciences, 2017)
Background: To analyse the clinical, radiological, laboratory, and bronchoscopic findings characterizing each type of bronchogenic carcinoma. Methods: A cross-sectional study was conducted on 123 bronchogenic carcinoma patients. They were subjected to history taking, laboratory investigations, computed tomographic scan and fiberoptic bronchoscopy. Results: The mean age of the patients was 56.9±6.7 years, 76.4% were males and 78.9% were smokers. Most of them were symptomatic, adenocarcinoma (ADC) being the highest symptomatic one. Expectoration, fingers clubbing, and fever were common in ADC and small cell lung cancer (SCLC). Dyspnea, haemoptysis, dysphonia, dysphagia, vocal cord paralysis, anorexia and weight loss were common in SCLC and squamous cell carcinoma (SCC). Deep venous thrombosis was common in ADC and SCC. Mass lesion, atelectasis, chest wall invasion and elevated hemidiaphragm were common in SCLC and SCC. Ipsilateral mediastinal lymph nodes enlargement, cavitary lesion, and apical lesion were common in SCC and ADC. Contralateral mediastinal lymph nodes enlargement was common in SCLC. Nodular lesion, consolidation and pleural effusion were common in ADC. Hypercalcemia and hyponatremia were common in SCC. Malignant pleural effusion was common in ADC. Most of the patients had bronchoscopically-visible lesions; SCLC and SCC being the highest visible types. Most of the SCC and SCLC were centrally located, while LCC and ADC were mainly peripherally located. Most of cases were diagnosed via bronchoscopy. More than half of the studied cases were inoperable at presentation, especially SCLC and SCC. Conclusions: The 4 pathological types are distinguished from each other’s by certain clinical, radiological, laboratory and bronchoscopic features.